Literasi Laporan Keuangan Sederhana bagi Ibu Rumah Tangga - Hafidhah Hafidhah; Edy Purwanto; Mohammad Herli; Miftahol Arifin; M. Munir Syam AR (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Pagerungan Besar Village is one of the villages in the Sapeken District with outstanding natural resource potential. This community service activity is essential, as many housewives still require financial literacy, particularly in managing household finances effectively. Two primary issues are identified: the lack of understanding of financial reports and the inability to prepare them. This activity aims to educate housewives on the benefits of financial reporting and offer training on creating financial reports. The activity was conducted on Monday, October 7, 2024, with 20 housewives participating. The socialization and training were held at a resident's house located on Jl. H. Mohammad Said, Pagerungan Besar Village, Sapeken District, Sumenep Regency. The method used was deemed appropriate for addressing the existing problems. The program consisted of three stages: preparation, implementation, and evaluation. Based on the outcomes observed during the activity, there was a noticeable improvement in the participants' understanding of simple financial reporting.